POLA PENGGUNAAN OBAT ANTIDIABETES PADA PASIEN JAMINAN KESEHATAN NASIONAL RAWAT JALAN DI RUMAH SAKIT UMUM DAERAH KOTA MATARAM TAHUN 2023 - Annisaturrahmah Himawan (LPPM, Akademi Administrasi Rumah Sakit Mataram, 2026)
Diabetes mellitus is a chronic disease characterized by metabolic disorders of carbohydrates, fats, and proteins due to insulin deficiency or resistance. The increasing prevalence of diabetes in Indonesia requires rational drug use, especially among National Health Insurance (JKN) patients. This study aims to determine the pattern of antidiabetic drug use in outpatients at Mataram City Regional General Hospital in 2023. This research used a descriptive method with a retrospective approach based on prescription data of JKN patients. The results showed that the most commonly used therapy was a combination of oral antidiabetic drugs, with metformin as the primary treatment. The use of combination therapy indicates efforts to optimize glycemic control. However, variations in drug use were still found, which may affect treatment effectiveness. In conclusion, the pattern of antidiabetic drug use among JKN outpatients in 2023 tends toward rational therapy but still requires continuous evaluation to improve healthcare quality.